A decision-making method for complex system design in a heterogeneous language information environment. (3rd June 2021) - Wang, Guan; Wu, Lingjiu; Liu, Yusheng; Ye, Xiaoping
Abstract : In the process of designing engineering systems, early system design often plays an important role. Although the existing system design methods are very effective, the preference information of different experts and the uncertainty of their subjective preferences are not processed effectively. Because different stakeholders have different backgrounds and different personalities, their linguistics preferences are expressed differently. Therefore, it is difficult to select a system scheme that meets all the performance requirements and is approved by various stakeholders. To solve this problem, a decision-making method is proposed in this study for complex system design in a heterogeneous language information environment. First, a theoretical system scheme set is constructed through a morphological matrix, and a multi-objective programming model is constructed based on the performance indicators to select the system scheme set that optimises each performance objective and meets the performance constraints. Then, a trapezoidal asymmetric cloud model is used as an intermediary for containing heterogeneous language information to integrate each stakeholder's preference information, as expressed by their favourite linguistic term sets, and to select the best system solution. The effectiveness of the proposed method is verified by a system design example of a horizontal directional drilling machine.